Peculiarities of Negation in Languages: The Example of Kola-Lapp - Szabó, László (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1988)
Answering a negative "yes" or "no" question, the Japanese say "yes" when we give a negative answer in English (and the other way around). The Latin double negation means a stressed positive statement. In Kola-Lapp (as well as in Hungarian and several other languages), double negation is definitely "negation" in the "logical" sense of the word. The principle of negation in Kola-Lapp is basically the same as in Finnish. There is a so-called verb of negation which is conjugated in person and number, while the stem or a certain form of the main verb is placed after the verb of negation. There are many idiomatic expressions which are formally negative constructions, but do not necessarily indicate that the action does not take place.